The fecal microbiota of the mouse-eared bat (Myotis velifer) with new records of microbial taxa for bats. - Hanya D Arellano-Hernández; Leslie M Montes-Carreto; José Antonio Guerrero; Esperanza Martinez-Romero (PLoS ONE)
Studies on the fecal microbiome of wild animals reveal valuable information on the feeding habits of the host and the possible roles of bacteria in digestion. In this work we characterized the fecal microbiota of seven male and seven female Myotis velifer bats using the V3-V4 regions of the 16S rRNA gene. Fecal samples were collected at the El Salitre cave in Mexico. We obtained 81 amplicon sequence variants, identifying four phyla, 12 families and 14 genera for females and seven phyla, 21 families and 26 genera for males. The phylum Synergistota is reported for the first time in bats. The most abundant phyla were Pseudomonadota and Fusobacteriota. Male feces showed a greater taxonomic richness than those from females. This study revealed that the fecal microbiota of M. velifer had a unique and more diverse composition compared to the microbiota reported for other bats. We identified 24 families and two abundant genera Cetobacterium and Haematospirillum in both males and females. Cetobacterium may produce vitamin B12 that is not produced by animals and Haematospirillum, which has been reported as an emerging human pathogen, may produce non-volatile organic acids. These genera had not been previously reported in the bat microbiota.